Analysis of Indonesia - China Bilateral Economic Sector in the Joko Widodo Era Against Indonesia's GDP - Mochamad Reza Irdiansyah; Soelistyo, Aris (Jurnal Ilmu Ekonomi JIE, 2024)
The research aims to analyze the effect of Foreign Debt, Investment, Exports, and Imports on Indonesia's GDP in the era of President Joko Widodo. The research here uses a quantitative approach, so it is done to collect only the object of research. Indonesia and China are the objects of research. The results of this study can conclude that foreign debt and exports are significantly positive in the rate of national GDP. At the same time, China-Indonesia investment and imports are insignificantly negative in Indonesia's GDP. In Indonesia-China, bilateral cooperation in the investment and import sectors does not greatly affect Indonesia's GDP. Meanwhile, the impact of the foreign debt and export sectors affects Indonesia's GDP.